Impact of Minimum Wage Policy on Job Satisfaction and Productivity in the Philippine Hospitality Sector - Jesus Briones; Charlve C Ortiz; Ivan P Lipit; Donabel F Montalbo; Maribel V Villaverde; Jonnette B Villamayor; Joanna Paula E Verano (Center for Risk Management & Sustainability and RSF Press, 2025)
Increasing the minimum wage primarily aims to reduce poverty, combat social inequality, boost employee productivity and improve the overall economic condition. This research aimed to understand the impact of minimum wage policy on employee job satisfaction and productivity in the Philippine hospitality sector. Using a quantitative descriptive research approach, the data were gathered from the 43 minimum wage earners performing various roles in a select hotel and resort in the Philippines. These respondents are a subpopulation of the 77 total employees in the company who have experienced the wage increase in September 2024. Using a researcher-structured questionnaire, responses were collected through a combination of face-to-face onsite surveys and Google Forms. Statistical tests such as frequency, percentage, weighted mean, and ANOVA were employed in the data analysis. The findings revealed that the minimum wage increases positively influenced employees’ job satisfaction and productivity with agreement across all areas. While the study confirmed the overall positive impact of the wage increase to the employees, most demographic factors were found not to affect their job satisfaction or productivity levels. Among demographic variables, educational attainment emerged as the only factor significantly influencing job satisfaction. Based on the findings, the researchers proposed a strategy roadmap to enhance the employees’ job satisfaction and productivity. This study can serve as reference for stakeholders in the hospitality sector, including human resource managers of hotels, resorts, and similar establishments who are seeking to improve employee satisfaction and drive overall productivity of the tourism industry.